Identifikasi Tipologi Kekumuhan Permukiman Pesisir Yang Rawan Abrasi Di Kabupaten Indramayu - Sri Tusnaeni Ningsih (Jurnal Planologi Unpas, 2016)
The coastal area is one area that is important to note in its construction, because about 60% of Indonesian people living in this area (Dahuri, 2002). Starting from these conditions, the coastal areas became the highest levels of poverty. It is equally the case in coastal Settlement Region in the village Eretan Kulon and Village Eretan, District Kandanghaur, Indramayu Regency. The area are home to coastal communities, and the average living standards of quality and coastal communities, including in low-income or disadvantaged, thus triggering more untidiness tinggkat again. The purpose of this study is to inform the planning of the slums and adaptive planning in coastal areas of Indramayu district to identify the typology slum settlements vulnerable coastal erosion in Indramayu. The results of this study are some areas along coastal settlements in the village Eretan Wetan Kulon and have a high to moderate untidiness typology, especially the typology high degree of untidiness in the settlement blocs on Eretan Kulon village. While the efforts to be made is with the relocation of the affected settlements indicated abrasi.Untuk not appropriate spatial restoration done by making buildings that are adaptive to disasters like floods and abrasion house form the stage for the tidal flood prone settlements. For the abrasion treatment efforts mangrove planting and construction of embankment either longitudinal or perpendicular to the beach.